2020
DOI: 10.2196/16253
|View full text |Cite
|
Sign up to set email alerts
|

Lock to Live—An Interactive Web-Based Lethal Means Safety Decision Aid for Suicidal Adults: Pilot Randomized Controlled Trial

Abstract: Background Counseling to reduce access to lethal means such as firearms and medications is recommended for suicidal adults but does not routinely occur. We developed the Web-based Lock to Live (L2L) decision aid to help suicidal adults and their families choose options for safer home storage. Objective This study aimed to test the feasibility and acceptability of L2L among suicidal adults in emergency departments (EDs). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…Alternatively, a broader focus allows greater reach to more patients, enhancing feasibility and potential suicide prevention value. Indeed, the adult L2L DA was expanded to address medication storage and translated to Spanish (20,21). However, this broader focus lengthens the DA with potential for reducing user acceptability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, a broader focus allows greater reach to more patients, enhancing feasibility and potential suicide prevention value. Indeed, the adult L2L DA was expanded to address medication storage and translated to Spanish (20,21). However, this broader focus lengthens the DA with potential for reducing user acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…Decision aids (DAs) can be developed as digital tools that can augment clinician interactions by offering patients education on potentially difficult decisions, considering their values and personal preferences (19)(20)(21). These clinical tools have been used to support complicated health-related decisions such as those involving medical treatments, end of life care, and disease screening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were a part of a larger study that created a patient-facing decision aid for reducing lethal means access in the context of suicide risk. [14][15][16] Participants were recruited through direct email invitations, posted flyers, and online advertisements. Eligible participants for the parent project were English-speaking, community-dwelling adults (≥ 18 years) in the United States who did not have active suicidal ideation and who belonged to ≥ 1 stakeholder group: those with "lived experience" of suicide risk (either themselves or a family member); suicide prevention professionals; ED providers; and firearm experts.…”
Section: Study Samplementioning
confidence: 99%
“…Additionally, VA clinicians can direct patients to Lock to Live, a decision support tool for those at risk of suicide that provides options for temporarily reducing firearm access. In a small pilot randomized clinical trial of adults at risk of suicide, 7 nearly all participants reported a willingness to recommend this website to others. While more participants in the Lock to Live study group reported a subsequent reduction in firearms access, a larger study will be needed to determine whether this promising result is statistically significant.…”
Section: Lethal Means Safety Training For Va Cliniciansmentioning
confidence: 99%